Turning Microbial AhR Agonists into Therapeutic Agents via Drug Delivery Systems - Matteo Puccetti; Marilena Pariano; Paulina Wojtylo; Aurélie Schoubben; Stefano Giovagnoli; Maurizio Ricci (MDPI AG, 2023)
Developing therapeutics for inflammatory diseases is challenging due to physiological mucosal barriers, systemic side effects, and the local microbiota. In the search for novel methods to overcome some of these problems, drug delivery systems that improve tissue-targeted drug delivery and modulate the microbiota are highly desirable. Microbial metabolites are known to regulate immune responses, an observation that has resulted in important conceptual advances in areas such as metabolite pharmacology and metabolite therapeutics. Indeed, the doctrine of "one molecule, one target, one disease" that has dominated the pharmaceutical industry in the 20th century is being replaced by developing therapeutics which simultaneously manipulate multiple targets through novel formulation approaches, including the multitarget-directed ligands. Thus, metabolites may not only represent biomarkers for disease development, but also, being causally linked to human diseases, an unexploited source of therapeutics. We have shown the successful exploitation of this approach: by deciphering how signaling molecules, such as the microbial metabolite, indole-3-aldehyde, and the repurposed drug anakinra, interact with the aryl hydrocarbon receptor may pave the way for novel therapeutics in inflammatory human diseases, for the realization of which drug delivery platforms are instrumental.